Relationship between learners’ L2 Motivational Self System and parental investment behavior in learners’ English learning - Zhang, Yu; Lu, Xiaobing; Liu, Honggang (Frontiers in Psychology, 2024)
Students' motivation and learning behavior are significantly impacted by parents' participation and investment (e.g., Schunk et al., 2014;Alawawda & Razi, 2020). It has been demonstrated that parental investment behavior could exert a direct effect on students' L2 Motivational Self System (L2MSS) mediated by parental investment belief (Liu, 2024). Nevertheless, the relationship between components of parental investment behavior and students' language learning motivation remains a topic necessitating further scholarly investigation. In response to this gap, we conducted a quantitative study involving a survey of 900 high school students to explore the relationship between students' English learning motivation, as conceptualized by the L2 Motivational Self System (Dörnyei, 2005), and parental investment behavior based on a four-component model (Liu, 2024). The findings in this study indicated that high school students exhibited moderate levels of L2MSS and relatively low levels of parental investment behavior. Moreover, students' L2MSS was found to have a significant positive correlation with the global parental investment behavior, with parental emotional investment behavior emerging as a positive predictor of high school students' L2MSS.These results underscore the importance of parental provision of sufficient economic, relationship, knowledge, and emotional support in cultivating a nurturing and supportive familial context conducive to the development of students' positive future 2 selves.